A Radioisotope Tracer Technique For The On-Stream Determination Of Simulation Parameters In Open-Cycle, Continuous Ball Mills ? 1. Introduction - Robin P. Gardner (Society for Mining, Metallurgy & Exploration, 1974)
The mechanistic approach to comminution consisting of incorporating particulate breakage functions into a suitable population balance equation has been developed by a number of researchers over the past decade or so. (1) To date this approach has been developed and demonstrated primarily for batch-operated, laboratory or small-scale ball mills. However, since industrial mills are mostly quite large and operated in the continuous mode; suitable population balance models and methods for obtaining the necessary breakage and other model parameters must be developed. This paper describes and investigates a radioisotope tracer technique for this purpose, Population balance models previously developed(2,3) are adapted for this study.